Measurement of ultralow heating rates of a single antiproton in a cryogenic penning trap - Borchert, Matthias Joachim; Quint, Wolfgang; Blaum, Klaus (Physical review letters, 2019)
We report on the first detailed study of motional heating in a cryogenic Penning trap using a single antiproton. Employing the continuous Stern-Gerlach effect we observe cyclotron quantum transition rates of 6(1) quanta/h and an electric-field noise spectral density below 7.5(3.4)×10−20 V2 m−2 Hz−1, which corresponds to a scaled noise spectral density below 8.8(4.0)×10−12 V2 m−2, results which are more than 2 orders of magnitude smaller than those reported by other ion-trap experiments.